Kinetic Study of Non-Isothermal Reactions on the Pyrolysis of Various Biomass Waste by using Thermogravimetric Data - Prasetiawan, Haniif; Fardhyanti, Dewi Selvia; Fatriasari, Widya; Hadiyanto, Hadiyanto (Universitas Negeri Semarang, 2023)
Population growth causes an increase in the need for petroleum. However, petroleum as primary energy is currently increasingly limited in availability. Required alternative energy sources that can be renewed to overcome these problems, one of which is bio-oil. Bio-oil is produced by a pyrolysis process using biomass such as sugarcane bagasse, rice husk, and empty oil palm fruit bunches (EFB), by heating in the absence of oxygen. Kinetic studies on pyrolysis of this type of biomass (sugar cane bagasse, rice husk, and empty oil palm fruit bunches) were carried out using the thermogravimetric method. The Coats-Redfern method was used in this study. The purpose of this study is to obtain the most appropriate reaction kinetics model to represent the pyrolysis process for each type of biomass. In addition, to determine the optimal temperature used in forming bio-oil. Approximately 5 g of each biomass is used with a heating rate of 10°C/minute. Pyrolysis was carried out until the temperature reached 750°C. The results of the research on the selected kinetic model for each biomass is a geometric model with a correlation coefficient (R2) close to 1 and the optimum temperature for producing bio-oil is around 550 - 600°C.